4. GOBLET CELLS IN NEOPLASTIC BARRETT MUCOSA AND THEIR RELEVANCE IN NEOPLASTIC PROGRESSION: A SEMIQUANTITATIVE ANALYSIS. (February 2015) - Bonavita, J.; Allanson, B. M.; Raftopoulos, S.; Kumarasinghe, M. P.
Abstract : Background: The trigger for screening of columnar lined mucosa (CLM) of oesophagus is the presence of histologically proven goblet cells (GC). There is some evidence that oesophageal adenocarcinoma (EAC) may arise in CLM without GCs. Pathological data on association of GCs and oesophageal glandular neoplasia is limited. Aim: Our aim was to assess the presence and the extent of GC metaplasia (EO-GCM) within CLM in association with glandular intraepithelial neoplasia/dysplasia (IEN) and early EAC in endoscopic resection (ER) specimens. Methods: A review was based on 64 cases of ERs from PathWest QEII Medical Centre. All ER specimens were entirely blocked and 59 showed IEN and/or EAC. A semi-quantitative assessment of EO-GCM in the CLM was done by dividing the length of CLM on each haematoxylin and eosin stained sections into 1 mm segments by estimation using on a single field of a 20× objective as approximately 1 mm. All 1 mm segments with GCs were aggregated per case as a % of the total length of all sections of CLM examined. The EO-GCM was correlated with the neoplastic phenotype and grade. Results: 56/59 (95%) IEN/EAC cases showed GCs in CLM. EO-GCM varied from 0–100% of the CLM. Phenotypically neoplastic component was pure intestinal in 5% and gastric or mixed types in the rest. Average EO-GCM in intestinal, gastric/foveolar and mixed phenotypes was 91%, 40% and 44% respectively. Low grade IEN, high grade IEN and EAC were 44%, 37% and 15% respectively. Conclusion: Majority of our cases show GCs within the neoplastic epithelium or in the background CLM. Extent of goblet cell metaplasia of CLM varied significantly in different phenotypes and grades of neoplastic epithelium.